Art and handicraft in the Woman's Building of the world's Columbian Exposition, Chicago, 1893 (The Gerritsen Collection - Women`s History Online, 1893)
Ednah Don Cheney and Julia Ward Howe were among those contributing articles to this book which describes the woman's exhibit at the world's Columbian exposition.